Adverse drug reaction reporting in a tertiary care teaching hospital of Eastern Odisha: a five-year retrospective study - Parida, Paramita; Misra, Debasish; Bose, Manika; Mishra, Swati (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Adverse drug reactions (ADRs) related morbidity and mortality is a concern as it reduces quality of life, prolongs hospital stay and inflicts significant burden on the healthcare resources. This study was under taken to evaluate the patterns of spontaneously reported ADRs, at an ADR monitoring centre (AMC) in a tertiary care teaching hospital in Eastern India. Methods: The present study was carried out for a period of five years from January 2020 to December 2024. Data were analysed for their demographic patterns, associated medications and reactions, system organ class affected, seriousness, outcomes and causality using the WHO causality scale. Mean, standard deviation, Chi-square ‘p’ and binomial ‘p’ were analysed. Results: Total ADRs reported was 500. Highest ADRs was in the group of 30-60 years (48.6%), females reporting was 52.4%. Maximum cases reported in 2024 (42%). Department of psychiatry reported maximum ADRs (17.8%). 51.8% cases reported possible causality. Rash was the most common ADR in 25.6% and ceftriaxone sulbactam combination caused 16% ADRs. The most affected system organ class was skin and subcutaneous tissue disorder (61%). Conclusions: The study depicted the pattern of reactions to various medications and helpful in augmenting the awareness of spontaneous reporting of ADRs amongst healthcare professionals, thereby enhancing patient safety and improving the quality of life.